Permasalahan Pancer dalam Karawitan Jawa Gaya Surakarta - Djoko Purwanto (Institut Seni Indonesia Surakarta, 2021)
This article discusses pancer in the Javanese traditional Javanese music presentation of the Surakarta style. The word pancer is also used in several Javanese philosophies of life. This paper tries to unravel the correlation of the concept of pancer in the life of the Javanese society with the Javanese traditional music of Surakarta style. In Javanese life, the concept of pancawara and saptawara are well known. Meanwhile, the Javanese karawitan of the Surakarta style uses the concept of five tones for sléndro and five tones for pélog although physically, in the pélog barrel it involves seven tones. The methods used in writing this article include literature study, musicology (karawitan) studies, social approaches, interviews, and observations as well as collecting several collections of recordings for analysis. In this case, the kempyung theory and the concept of Martopangrawit's tone strength as well as the pathet concept (biang pathet in the laras sléndro) by Sri Hastanto are used as analytical tools. The results of the analysis found that not all notes in karawitan can be used as pancer. Pancer in Javanese philosophy represents the life link of the Javanese people, while pancer in karawitan shows the character and the sense of gending.